Oxidative Metabolism of Rye (Secale cereale L.) after Short Term Exposure to Aluminum: Uncovering the Glutathione–Ascorbate Redox Network - de Sousa, Alexandra; AbdElgawad, Hamada; Han, Asard; Teixeira, Jorge; Matos, Manuela; Fidalgo, Fernanda (Frontiers in Plant Science, 2016)
One of the major limitations to plant growth and yield in acidic soils is the prevalence of soluble aluminum ions (Al3+) in the soil solution, which can irreversible damage the root apex cells. Nonetheless, many Al-tolerant species overcome Al toxicity and are well adapted to acidic soils, being able to complete their life cycle under such stressful conditions. At this point, the complex physiological and biochemical processes inherent to Al tolerance remain unclear, especially in what concerns the behavior of antioxidant enzymes and stress indicators at early plant development. Since rye (Secale cereal L.), is considered the most Al-tolerant cereal, in this study we resort to two genotypes with different Al sensitivities in order to evaluate their oxidative metabolism after short term Al exposure. Al-induced toxicity and antioxidant responses were dependent on rye genotype, organ and exposure period. Al affected biomass production and membrane integrity in both organs of the sensitive (RioDeva) genotype. Catalase was the primary enzyme involved in H2O2 detoxification in the tolerant (Beira) genotype, while in RioDeva this task was mainly performed by GPX and POX. Evaluation of the enzymatic and non-enzymatic components of the ascorbate-glutathione cycle, as well the oxalate content, revealed that Beira genotype coped with Al stress by converting DHA into oxalate and tartarate, which posteriorly may bind to Al forming non-toxic chelates. In contrast, RioDeva genotype used a much more ineffective strategy which passed through ascorbate regeneration. So, remarkable differences between MDHAR and DHAR activities appear to be the key for a higher Al tolerance.